ANALISIS PERENCANAAN PADA PENINGKATAN RUAS JALAN RAYA CIREBON – SUMBER (JL. PANGERAN CAKRABUANA) KABUPATEN CIREBON - Rival Rival; Martinus Agus; Shinta Novriani (Teknik Sipil, Politeknik Negeri Ketapangg, 2023)
A road segment is a path that aims to pass traffic from one place to another. Good road pavement construction conditions must be able to fulfill functional requirements, namely providing a sense of security and comfort as well as minimum travel time for road users. This study aims to analyze the traffic performance on the Cirebon - Sumber road, then plan improvements to the pavement and road geometry to improve traffic performance. The method used in this study is a quantitative method using the 1997 Indonesian Road Capacity Manual (MKJI), then planning pavement and widening based on the current LHR using the 2017 Pavement Design Manual (MDP) method. In order to accommodate vehicle volumes of up to 25 next year, the road width is planned to be 11 meters, namely 5.5 m for each lane with a 2/2 UD road type. From the results of calculating the thickness of the rigid pavement using the 2017 method (MDP), a pavement thickness of 28.5 cm is obtained and can accommodate the number of passing vehicles with the degree of sturation of 0.63 with Level of Service C (Stable Flow).